METODE MONTESSORY UNTUK MENINGKATKAN SELF ESTEEM PADA SISWA SLOW LEARNER - Yussi Martha Sukma Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2022)
Slow learner students are students who experience delays in the learning process. This delay affects other abilities such as adaptation, communication and personality which can have an impact on self-esteem. Students with high self-esteem make them able to think positively about themselves and be more confident. One form of handling to increase self-esteem is using the Montessory method. This method helps students explore themselves through play media. The purpose of this research is to identify the needs of slow learner students with low self-esteem towards the Montessory method in learning.